2022
DOI: 10.1161/circresaha.122.321036
|View full text |Cite
|
Sign up to set email alerts
|

LPA 2 Contributes to Vascular Endothelium Homeostasis and Cardiac Remodeling After Myocardial Infarction

Abstract: Rationale: Myocardial infarction (MI) is one of the most dangerous adverse cardiovascular events. Our previous study found that lysophosphatidic acid (LPA) is increased in human peripheral blood after MI, and LPA has a protective effect on the survival and proliferation of various cell types. However, the role of LPA and its receptors in MI is less understood. Objectives: To study the unknown role of LPA and its receptors in heart during MI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…After further addition of pDA/nHA, the BV/TV value of PP-pDA/nHA-LPA increased by 17.1% to PP-LPA, signifying that the addition of nHA could improve the osteogenesis effect of LPA, and the two could synergistically promote osteogenesis in vivo . In addition, some studies have shown that LPA2 and LPA6 signaling could promote angiogenesis and maintain vascular homeostasis, which is a key part of tissue repair. , This synergistic effect was possibly due to the stable LPA accelerating the migration of osteoblasts while superimposing the properties of HA to promote the proliferation and differentiation of osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After further addition of pDA/nHA, the BV/TV value of PP-pDA/nHA-LPA increased by 17.1% to PP-LPA, signifying that the addition of nHA could improve the osteogenesis effect of LPA, and the two could synergistically promote osteogenesis in vivo . In addition, some studies have shown that LPA2 and LPA6 signaling could promote angiogenesis and maintain vascular homeostasis, which is a key part of tissue repair. , This synergistic effect was possibly due to the stable LPA accelerating the migration of osteoblasts while superimposing the properties of HA to promote the proliferation and differentiation of osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some studies have shown that LPA2 and LPA6 signaling could promote angiogenesis and maintain vascular homeostasis, which is a key part of tissue repair. 64,65 This synergistic effect was possibly due to the stable LPA accelerating the migration of osteoblasts while superimposing the properties of HA to promote the proliferation and differentiation of osteoblasts.…”
Section: Alizarin Red Staining Assaymentioning
confidence: 99%
“…In addition, EGFR inhibition results in ventricular hypertrophy, dilation, and impaired cardiac function in adult murine hearts 20 . PI3K/Akt pathway activation protects against cardiac remodeling 5,21 . Meanwhile, activating the mTORC2‐Akt pathway improves cardiac function after ischemic damage 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] Notably, PCSK9 (proprotein convertase subtilisin/kexin 9) inhibitors have shown significant reductions in plasma Lp(a) concentration, which may lead to improved coronary outcomes. [27] Pei et al [28] have experimentally demonstrated the potential clinical therapeutic value of targeting LPA-LPA2 to protect the heart from ischemic injury, warranting further clinical attention. Furthermore, APOA5 is believed to be the gene exerting the strongest influence on TG metabolism.…”
Section: Discussionmentioning
confidence: 99%